Mort - Pratchett, Terry (London : Victor Gollancz LTD, in association with Colin Smythe Ltd., 1987)
Mort has been chosen as Death's apprentice. He gets board and lodging and free use of the company horse, and doesn't even need time off for his grandmother's funeral. The trouble begins when instead of collecting the soul of a princess, he kills her would-be assassin, and changes history.
Keywords: Discworld (Imaginary place) -- Fiction; Discworld (Imaginary place); Fiction in English, 1945- - Texts; Fantasy fiction; Fiction; Humorous fiction; Fantasy fiction